FIRST FOSSIL RECORD OF PLIOMETANASTES SP. (MAMMALIA, XENARTHRA, MEGALONYCHIDAE) FROM THE UPPER MIOCENE OF COSTA RICA, CENTRAL AMERICA. A NEW CLUE TO UNDERSTAND THE PRE-GABI - Laurito, César A. (2011)
Two lower molar teeth and a unique postcranial remain of Pliometanastes cf. P. protistus Hirschfeld &Webb, 1968, are described from the San Gerardo de Limoncito Locality (Early Hemphillian) in the Curré Formationnear of the town of San Vito, Southern Costa Rica.This found changes our vision about the route of dispersion of the earliest South American mammals that reachedNorth America and confirms the Costa Rican-Panama Island Arc like the most effective path of migration in spite ofthe relatively broad ocean gaps.